Adaptasi Kebiasaan Baru Selama Pandemic melalui Upaya Peningkatan Produktifitas Wirausaha Mandiri Menuju Ekonomi Berkeadilan - Yuliani, Nafisah; Pramestari, Diah; Henni, Henni (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2021)
Abstrak-This study aims to determine the efforts to increase the productivity of independent entrepreneurs towards a just economy as a form of adaptation during a pandemic. The sample consists of students who already have a business or who do not have a business as many as 137 students. The data was collected through a mail survey (google forms) and analyzed by descriptive method to find out the description of the respondents to the problem under study. The results of this study indicate that efforts to increase entrepreneurial productivity through improving the characteristics of superior entrepreneurs, improving marketing strategies and improving business performance are a new form of adaptation during the pandemic in order to realize independent entrepreneurship towards a just economy. The results of this study also have two implementations: (1) theoretical implementation for the results of this study is to realize independent entrepreneurship towards a just economy, then the application of competitive strategies in the form of Cost Leadership Strategy, Differentiation Strategy, Innovation Strategy ( Innovation Strategy), Growth Strategy, Alliance Strategy, (2) managerial implementation for the results of this study is an effort to increase entrepreneurial productivity through improving the characteristics of superior entrepreneurs, improving marketing strategies and improving business performance as a form of adaptation. only during the pandemic to realize independent entrepreneurship towards a just economy. This provides motivation to survive in the midst of high competition with good ICT mastery and expand overseas Keywords: Adapting to New Habits, Productivity, Self-Employment